Mosaic trisomy 17 at amniocentesis: Prenatal diagnosis, molecular genetic analysis, and literature review - Chih-Ping Chen; Liang-Kai Wang; Schu-Rern Chern; Yen-Ni Chen; Shin-Wen Chen; Peih-Shan Wu; Dai-Dyi Town; Chen-Wen Pan; Chien-Wen Yang; Wayseen Wang (Elsevier, 2016)
Objective: We present prenatal diagnosis and molecular genetic analysis of mosaic trisomy 17 and a review of the literature of mosaic trisomy 17 at amniocentesis. Materials and Methods: A 42-year-old woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age, which revealed a karyotype of 47,XX,+17[4]/46,XX[17]. Prenatal ultrasound findings were unremarkable. She underwent repeat amniocentesis at 20 weeks of gestation. Interphase fluorescence in situ hybridization (FISH), array comparative genomic hybridization, and quantitative fluorescent polymerase chain reaction assays were applied to uncultured amniocytes. Conventional cytogenetic analysis was applied to cultured amniocytes and cord blood. Interphase FISH was applied to uncultured urinary cells postnatally. Results: At repeat amniocentesis, molecular genetic analysis of uncultured amniocytes revealed no genomic imbalance in array comparative genomic hybridization, no uniparental disomy 17 in quantitative fluorescent polymerase chain reaction, and 4.7% (5/105 cells) mosaic trisomy 17 in interphase FISH analysis. Conventional cytogenetic analysis of cultured amniocytes revealed a karyotype of 46,XX (17/17 colonies). A phenotypically normal baby was delivered at 38 weeks of gestation. The cord blood had a karyotype of 46,XX. Interphase FISH analysis of uncultured urinary cells revealed 5.6% (5/90 cells) mosaic trisomy 17. The neonate manifested normal growth and psychomotor development during follow-ups. Conclusion: Low-level mosaicism for trisomy 17 detected by amniocentesis without ultrasound abnormality can be associated with a favorable outcome. Molecular genetic analysis of uncultured amniocytes at repeat amniocentesis is useful for genetic counseling. A review of the literature shows a correlation between an adverse fetal outcome and a higher trisomy 17 mosaicism level at amniocentesis associated with ultrasound abnormality.